2017
DOI: 10.1017/s0031182017001755
|View full text |Cite
|
Sign up to set email alerts
|

The helminth community of a population ofRattus norvegicusfrom an urban Brazilian slum and the threat of zoonotic diseases

Abstract: Urban slums provide suitable conditions for infestation by rats, which harbour and shed a wide diversity of zoonotic pathogens including helminths. We aimed to identify risk factors associated with the probability and intensity of infection of helminths of the digestive tract in an urban slum population of Rattus norvegicus. Among 299 rats, eleven species/groups of helminths were identified, of which Strongyloides sp., Nippostrongylus brasiliensis and, the human pathogen, Angiostrongylus cantonensis were the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 73 publications
(119 reference statements)
1
28
0
1
Order By: Relevance
“…was present in 97% of the rats (Carvalho‐Pereira et al. ), we investigated whether its mean intensity varied in the presence or absence of other parasite species, regardless of the simple association tests for presence. We found that the intensity of Strongyloides sp.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…was present in 97% of the rats (Carvalho‐Pereira et al. ), we investigated whether its mean intensity varied in the presence or absence of other parasite species, regardless of the simple association tests for presence. We found that the intensity of Strongyloides sp.…”
Section: Resultsmentioning
confidence: 99%
“…The demographic features of the Pau da Lima rat population have been described by Carvalho‐Pereira et al. ().…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations